COLLISIONAL VOLCANISM OF CAUCASIAN SECTOR IN ALPINE FOLDED BELT - Koronovsky Н.; Demina, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Subaerial volcanism within the Caucasian segment of the Alpine fold-and-thrust belt has occurred in overall meridional compression up to the present time. Collisions characteristic of the Late Miocene changed the nature of subduction and caused a complex pattern of extensional stress fields, with SW and SE shear zones, sublatitudinal shears, and thrusts of the Caucasian orientation being predominant. There are singled out meridional compression areas to match local areas of extensional shear zones. Surficial manifestations of volcanism are commonly linked to the environments of local extension into regional area of submeridional compression. Collisional volcanites relating generally to the calc-alkaline series have geochemical features characteristic of both subduction zone rocks and continental rift rocks. The ratio of Si, K, Mg and Ti oxides on the ternary diagram shows collisional volcanites proper to be located between the fields of subductional volcanites and volcanites of continental rifts. Collisional volcanites have distinctive geological features: 1) Minor manifestation of fractional crystallizations (if any). 2) Antidromic sequence of volcanic eruptions (decrease in the silica content and increase in alkalinity). 3) High concentration of non-coherent and LRRE elements in basic rocks. 4) Low depths of basaltic magma generation. 5) Considerable lateral heterogeneity in the chemical composition of volcanites. Tholeiites tend to increase southwards, while geodynamic environment evolves in continental rifting. The principal reason for lateral heterogeneity could be found in various types of melting, metasomatism, substratum and crystalline basement, change of pressure-temperature conditions, and magma chambers. Andesite-dacite melts undergo subsequent heating from 750-850°С to 1150°С and an increase in the internal pressure from 0.6-0.8 GPa to 1.5 GPa. The basalts of the Caucasian segment, compared with the basalts of other geodynamic environment, are significantly enriched with Zr, which allows including fields of continental collisional volcanites to common discriminative Zr-Ti, Zr-Y, Zr-Ti-Y diagrams. There is a geochemical distinction between continental collisional volcanites of the Caucasus and suprasubduction rocks of the island arcs – a decrease in LREE content and differentiation shifting from basic to acid rocks.